2001
DOI: 10.1523/jneurosci.21-23-09175.2001
|View full text |Cite
|
Sign up to set email alerts
|

Species-Specific Differences in Expression of G-Protein-Coupled Receptor Kinase (GRK) 7 and GRK1 in Mammalian Cone Photoreceptor Cells: Implications for Cone Cell Phototransduction

Abstract: Desensitization plays an important role in the rapid termination of G-protein signaling pathways. This process, which involves phosphorylation by a G-protein-coupled receptor kinase (GRK) followed by arrestin binding, has been studied extensively in the rod photoreceptor cell of the mammalian retina. In contrast, less is known regarding desensitization in cone photoreceptor cells, which occurs more rapidly than in rod cells. Recently, our laboratory has cloned a novel GRK family member, GRK7, from the retina o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
132
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(137 citation statements)
references
References 48 publications
5
132
0
Order By: Relevance
“…The higher expression and specific activity of GRK7 compared with GRK1 (43) create the potential for much higher rate of pigment phosphorylation in cones compared with rods. In the mouse retina, GRK1 is the only kinase expressed in rods and cones (30). A study with the cone-like photoreceptors in the Nrl Ϫ/Ϫ mouse has demonstrated that mammalian cone opsin is phosphorylated upon light activation (44).…”
Section: Discussionmentioning
confidence: 99%
“…The higher expression and specific activity of GRK7 compared with GRK1 (43) create the potential for much higher rate of pigment phosphorylation in cones compared with rods. In the mouse retina, GRK1 is the only kinase expressed in rods and cones (30). A study with the cone-like photoreceptors in the Nrl Ϫ/Ϫ mouse has demonstrated that mammalian cone opsin is phosphorylated upon light activation (44).…”
Section: Discussionmentioning
confidence: 99%
“…CYGX is implicated in olfaction (25), and its loss in human parallels that of other olfactory genes. Similarly, the loss in mouse of GPRK7, a potential cone opsin kinase, correlates with the reduced color vision of rodents (26). Cell cycle-related kinases (CDK3 and PLK5) are less likely candidates for gene loss and may indicate redundancy in cell cycle machinery.…”
Section: Discussionmentioning
confidence: 99%
“…Photoreceptors respond to light stimuli within milliseconds and rapidly terminate signaling to recover and maintain their sensitivity under constantly changing ambient light. In rods, G protein-coupled receptor kinase 1 (GRK1) 3 contributes to signal turnoff via phosphorylation of rhodopsin, the G protein-coupled receptor that initiates the phototransduction cascade. Phosphorylation is followed by the binding of arrestin to rhodopsin, which sterically blocks the interaction of rhodopsin with its G protein, transducin (1,2).…”
mentioning
confidence: 99%
“…Phosphorylation is followed by the binding of arrestin to rhodopsin, which sterically blocks the interaction of rhodopsin with its G protein, transducin (1,2). GRK1 is expressed in rods of all vertebrates and in cones in several vertebrates (3). For example, GRK1 is expressed in both rods and cones in mice, where it phosphorylates rhodopsin and the cone opsins, respectively (4 -6).…”
mentioning
confidence: 99%